Depiction of Colonial Indian Women in Jim Corbett’s ‘My India’ - Indrajit Kamble; Gangubai/Shashikala. D. Ingale; Uttam Pandurang Jadhav (Emerging Trends in Languages, 2023)
Jim Corbett was a domiciled British who were working as a fuel inspector and later as transshipment contractor in Mokameh Ghat in colonial India. In his all books the reflection of contemporary cultural, social, religious Indian is found. There are also some woman characters mentioned in his books. The book My India is a picture gallery of Indian characters with whom Corbett has came across during his work period and his expeditions to hunt down the man-eaters. This article will observe the positive and negative stance of Corbett. It will be observed whether this representation of colonial Indian woman is truthful or not. This characteristic is visible in Corbett’s writing. He provided details about how Anderson, Ramsay and other British administrators were doing justice to the orients and how the application of red tape rules hindered the authority of the British Officials. Corbett features authentic cultural data to European readers. This particular marriage custom is depicted as the flaw of the Indian society that does not offer freedom to people to choose their life partner. Thus, a drawback is highlighted in this story. One more characteristic is conspicuous in representing Indian character that is use of adjectives. When a writer uses some adjectives regarding his people these adjectives, they considered as the characteristics of those people. The adjectives that are used in depicting Indians are ‘poor, terror stricken, fearful, selfish, illogical, exacerbating and superstitious’, etc. These adjectives are negative words and create a negative impression of Indians.
Keywords: Culture; Indian; Jim Corbett; colonial woman; colonialism; my India; orientalism; postcolonial